Combining agreement and frequency rating scales to optimize psychometrics in measuring behavioral health functioning. - Marfeo, Elizabeth E.; Ni, Pengsheng.; Chan, Leighton.; Rasch, Elizabeth K.; Jette, Alan M. (Tufts University. Tisch Library., 2017)
Objective: The goal of this article was to investigate optimal functioning of using frequency vs. agreement rating scales in two subdomains of the newly developed Work Disability Functional Assessment Battery: the Mood & Emotions and Behavioral Control scales. Study Design and Setting: A psychometric study comparing rating scale performance embedded in a cross-sectional survey used for developing a new instrument to measure behavioral health functioning among adults applying for disability benefits in the United States was performed. Results: Within the sample of 1,017 respondents, the range of response category endorsement was similar for both frequency and agreement item types for both scales. There were fewer missing values in the frequency items than the agreement items. Both frequency and agreement items showed acceptable reliability. The frequency items demonstrated optimal effectiveness around the mean ± 1-2 standard deviation score range; the agreement items performed better at the extreme score ranges. Conclusion: Findings suggest an optimal response format requires a mix of both agreement-based and frequency-based items. Frequency items perform better in the normal range of responses, capturing specific behaviors, reactions, or situations that may elicit a specific response. Agreement items do better for those whose scores are more extreme and capture subjective content related to general attitudes, behaviors, or feelings of work-related behavioral health functioning.